2007
DOI: 10.1590/s0004-282x2007000200029
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioneuroblastoma of the cerebellum: neuroimaging and pathological features of a case

Abstract: The MRI findings of our case showed no features which could help in the differentiation between ganglioneuroblastoma and the other common types of posterior fossa neoplasms in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…It was reported that the longest asymptomatic period of the patients with intracranial GNB is 60 months following the above treatment. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the longest asymptomatic period of the patients with intracranial GNB is 60 months following the above treatment. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…This explains that patients with this subtype are likely to be offered surgery and benefit from surgical excision with overall better survival. Ganglioneuroblastoma typically has a high invasive behaviour but slower multiplication rate and the asymptomatic period of up to 60 months has been reported after surgical excision [35,36].…”
Section: Management Optionsmentioning
confidence: 99%
“…Upon reviewing the literature for pediatric cases of primary intracranial ganglioneuroblastomas, we identified 10 patients reported in the English and French literature [2][3][4][5][6][7]. Reported intracranial tumors most commonly arise in the parietal lobe and cerebellum with symptoms of increased intracranial pressure; only one case involved the occipital lobe [2].…”
mentioning
confidence: 99%
“…With this treatment combination, the patient had a favorable clinical course without tumor recurrence for more than 60 months. Survivals were reported in three of the 10 previously reported patients at 7 months, 26 months, and 36 months [5][6][7]. The range of survival after initial symptoms was 0.7-36 months (median 11 months), which is substantially less than the 60% 3 year survival in pediatric patients with cerebral neuroblastomas [8].…”
mentioning
confidence: 99%